Evaluation of Oxidative Stress in Cutaneous Leishmaniasis in Iraqi Patients - Mohammed K. Al-Hattab; Noor H. Nahi; Jinan H. Al-Kalidi (Medical Journal of Babylon)
Background:This study evaluated the oxidative—antioxidative status of patients with cutaneous leishmaniasis (CL) and to establish the data alteration among the patients and the control. Objectives:To determine serum levels of malondialdehyde (MDA), serum uric acid (UA), and catalase enzyme as a markers of oxidative stress in the patients suffering from CL. Materials and Methods:A total of 46 patients with CL (22 males and 24 females) aged between 5 and 60 years were subjected to investigations. Out of the total sample, 42 healthy persons (28 males and 14 females) functioned as control group, patients who received anti-leishmaniasis treatment locally or systemically for their cutaneous lesions and also patients with chronic history of medical disease or drug history for systemic or dermatological diseases were not included in this study. Results:For comparative evaluation of oxidative stress markers between patients and control; there were a significant increase in lipid peroxidation marker; serum MDA and non-enzymatic antioxidant marker—serum UA in the patient group in comparison to the control group, with non-significant decrease in enzymatic antioxidant—serum catalase enzyme in patients as compared with control groups. There is negative significant relationship for decrease of catalase enzyme for patients with CL above age of 15 years. The study of the patients with CL that is, associated with secondary bacterial infection shows a significant decrease in serum catalase enzyme when compared with control group. Conclusions:1. The results of this study clearly demonstrate the importance of serum MDA as an early biochemical indicator of peroxidative damage resulting from CL. 2. Increased serum UA, and decrease in serum catalase enzyme provided a free radical scavenger’s action.